Traditional gender roles of men and women in natural resource conservation among the Vhavenda people in Zimbabwe: implications for sustainable development - Mukoni, Manuku (Center for Promoting Ideas, 2017)
A publication by Mrs Manuku Mukoni a Lecturer in the Department of Gender Studies, Midlands State University, Zimbabwe